Fecal microbiota associated with phytohaemagglutinin-induced immune response in nestlings of a passerine bird - Kreisinger, Jakub; Schmiedová, Lucie; Petrželková, Adéla; Tomášek, Oldřich; Adámková, Marie; Michálková, Romana; Martin, Jean-François; Albrecht, Tomáš (Ecology and evolution, 2018)
The vertebrate gastrointestinal tract is inhabited by a diverse community of bacteria, the so-called gut microbiota (GM). Research on captive mammalian models has revealed tight mutual interactions between immune functions and GM. However, our knowledge of GM versus immune system interactions in wild populations and nonmammalian species remains poor. Here, we focus on the association between GM community structure and immune response measured via the phytohaemagglutinin (PHA) skin swelling test in 12-day-old nestlings of a passerine bird, the barn swallow (Hirundo rustica). The PHA test, a widely used method in field ecoimmunology, assesses cell-mediated immunity. GM structure was inferred based on high-throughput 16S rRNA sequencing of microbial communities in fecal samples. We did not find any association between PHA response and GM diversity; however, our data revealed that the intensity of PHA response was correlated with differences in GM composition at the whole-community level. Ten bacterial operational taxonomic units corresponding to both putative commensal and pathogens were identified as drivers of the compositional variation. In conclusion, our study suggests existence of GM versus immune system interactions in a free-living nonmammalian species, which corresponds with previous research on captive vertebrates.
Keywords: inflammation; symbiosis; fitness; microbiome; metabarcoding; immunity